Identifikasi Distinctiveness sebagai Faktor Pembentuk Place Identity di Kampung Kauman Surakarta - Aminaturosyida Rahma Wardhani; Avi Marlina; Untung Joko Cahyono (Arsitektura : Jurnal Ilmiah Arsitektur dan Lingkungan Binaan, 2025)
Identification of Distinctiveness as a Factor in Shaping Place Identity at Kampong Kauman SurakartaRegardless of its scale, each place has an identity shaped by defining attributes, including its distinctiveness. Kauman Surakarta is a historic area that is increasingly pressured by modernization and shifting community lifestyles, potentially diminishing its distinct character. Therefore, identifying the distinctive elements that continue to shape the identity of Kauman Surakarta is essential. This study employs a quantitative approach through the distribution of questionnaires to visitors. The findings show that the Grand Mosque ranks as the primary landmark of Kauman Surakarta, and visitors demonstrate a relatively strong awareness of its unique features. The narrow alleys, heritage walks, and traditional hand-drawn batik products emerge as the most appealing characteristics. Visitors reported positive impressions that encourage their intention to return. These results are expected to support stakeholders in ensuring the sustainability and preservation of Kauman Surakarta’s identity.